Bibliometric Mapping of the Mathematics Role in Daily Life - Ahmad Iswanto; Asma Ul Husna; Kristianti Kristianti; Kiki Amalia; Nur Kurniyasih; Muntazhimah Muntazhimah (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
This study aims to analyze the bibliometric mapping the mathematics' role in everyday life. This study uses a qualitative method by comparing the information obtained from a Google Scholer search. This method is entirely based on the hunt for journal articles developed through bibliometric analysis. Data was collected using Publish or Perish (PoP) and visualized using VOSviewer. In this study, researchers obtained metadata from as many as 995 articles of applied mathematics in everyday life published on April 15, 2022, using a database of 1000 articles from 1926 to 2022. The results and discussion of the bibliometric analysis that has been carried out show that this research topic is still possible. Other researchers for the next period because the data that has been analyzed is still categorized as feasible, and there are still few studies related to bibliometric mapping of the role of mathematics in everyday life. Then suggestions for further research if researchers are interested in choosing a research topic on bibliometric mapping of the role of mathematics in everyday life, namely by connecting various other activities in society and combining it with the progress that developed during the research period so that the data obtained is always up-to-date to evaluate the effectiveness of mathematics in daily life